Využití umělé inteligence pro vyhodnocení bonity firmy - Šustrová, Tereza (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce se zabývá návrhem modelu pro vyhodnocení bonity firmy z pohledu věřitele za použití umělé inteligence. Model je zpracován v programu MS Office Excel a MathWorks Matlab s využitím teorie fuzzy logiky.

This master thesis deals with a proposal of a model for a company’s creditability evaluation from a view of a creditor using artificial intelligence. The model is developed in MS Office Excel and MathWorks Matlab utilizing the fuzzy logic theory.
The Application of Fuzzy Logic for Company's Creditability Evaluation
Keywords: Rozhodování; fuzzy logika; bonita firmy; věřitelé; finanční ukazatele; MathWorks Matlab; Decision making; fuzzy logic; company’s creditability; creditors; financial indicators; MathWorks Matlab